(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Introduction: Infertility affects 9–18% of the population, with vitamin D deficiency being a potential contributing factor. This study evaluates the association between vitamin D levels and primary Infertility in women attending a tertiary care centre in Southeast Bangladesh. Methods: A cross-sectional study was conducted at Chittagong Medical College Hospital’s(CMCH) Infertility Unit over one year( February 2020 to January 2021). Ninety-two women with primary Infertility were recruited based on specific inclusion criteria. Data collection included demographic details, clinical history, hormonal profiles, and vitamin D levels measured via Chemiluminescent Microparticle Immunoassay. Vitamin D status was classified according to the 2011 Endocrine Society guidelines. Statistical analysis was performed using SPSS version 23. Results: All the participant’s Vitamin D level were found less than normal. The majority (75%) of women had insufficient (<30 ng/ml) vitamin D levels, with 14.1% classified as severely deficient (<10 ng/ml). Vitamin D deficiency was significantly associated with urban residence and limited sun exposure (p=0.021). Clinical characteristics revealed 45.7% of participants had PCOS, and a significant portion displayed obesity (BMI ≥25 kg/m²). Hormonal analysis highlighted elevated LH levels in 44.8% and low AMH in 13.5%. Discussion: Vitamin D deficiency was highly prevalent among infertile women, supporting its potential link to reproductive dysfunctions such as ovulatory disorders. PCOS and metabolic abnormalities further compounded infertility risks. These findings align with global studies, suggesting vitamin D supplementation as a promising adjunct in infertility management. Conclusion: Vitamin D deficiency is a significant concern in women with primary Infertility in Bangladesh. The study emphasizes the need for targeted interventions, including supplementation and lifestyle modifications, to improve reproductive outcomes. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 104-110